New species of Telegeusis (Coleoptera: Telegeusidae) from northern Mexico - Oscar Pérez-Flores; Santiago Zaragoza-Caballero (Revista Mexicana de Biodiversidad)
The genus Telegeusis Horn is the most diverse of the family Telegeusidae, with 16 described species, most of them distributed in Mexico (13 species). Herein, we describe 4 new species based on material collected from Tamaulipas, Mexico: T. cieloensis sp. nov., T. estebani sp. nov., T. flavafusca sp. nov., and T. luismartinezi sp. nov. Distinguishing characters from closely related species are given and discussed, and the key for the species of the genus is updated.